Focusing Adverbs in Medical Academic Discourse - ازهار حسين عباس (آداب الكوفة, 2013)
In any communication , it is essential to focus upon certain parts of the message to achieve complete understanding. One way is by employing 'focus-ing adverbs' –the main concern of this study. Focusing adverbs are those that  focus on a particular part of the sentence. The study aims at (a) presenting the theoretical literature on meanings, syntactic properties, and functions of focus-ing adverbs (b)Identifying the meaning and characteristics of medical academic discourse (c)Finding out the employment of focusing adverbs in the medical academic discourse. Focusing adverbs are four categories: Additives, particularizers, exclusives (or restriction adverbs) and  intensifiers.Their  main  syntactic function is  modifiers of what they precede( adjective, adverb or main verb). Academic discourse has certain features: responsible, hedged, explicit, objective, formal, complex and persuasive. Focusing adverbs employed in this discourse show the importance of the parts  of the sentences. This is essential as it draws the attention to the important things in the delivered message. The study finds that the most employed category of focusing adverbs in medical academic discourse is the intensifiers(such as largely,considerably,ad mainly ) then, particularizers (e.g. particularly), additives ( such as neither …nor and either…or) and exclusives(e.g. exclusively)respectively .While the most employed adverbs are particularly, especially, either… or and mainly respectively.